FEATURES OF THE COURSE OF CHRONIC CORONARY SYNDROMES IN PATIENTS WITH CORONAVIRUS DISEASE - Tomyn, I. V.; Fedorov, S. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2022)
The new coronavirus disease COVID-19, caused by the SARS-CoV-2 virus, has put an unprecedented strain on the health care system and is one of the leading infectious diseases in terms of the prevalence and development of complications in various body systems. Among the main risk factors that negatively affect the course of COVID-19: age over 65 years, coronary artery disease (CAD), chronic heart failure (CHF), arrhythmias, chronic obstructive pulmonary disease (COPD), smoking and more. The existing results of observational studies on the mutual burdened effects of coronavirus disease on CVD in general and chronic coronary syndromes (CCS) are often contradictory, which requires further research in this area. The aim was to study the features of the clinical course of coronavirus disease COVID-19 in patients with chronic coronary syndromes. 75 inpatients were treated for COVID-19 coronavirus disease complicated by pneumonia. Patients were divided into two groups: the study group, which included 51 patients with CCS, and the control group, which included 24 patients without a history of CCS. Conducted physical and general clinical examination. The obtained results indicate a probable increase in the manifestations of shortness of breath, chest pain in patients with CCS, which may be evidence of destabilization of coronary atherosclerosis. Interestingly, there is a marked increase in the incidence of olfactory and taste disorders in patients with COVID-19 with concomitant CCS. It was noted that the available CCS increased the length of hospital stay of patients with coronavirus disease, as well as the need for oxygen support; there is a tendency to increase the risk of death in such patients. There was no significant difference in the levels of PSA, procalcitonin, D-dimer in the examined groups.So, chronic coronary syndromes in patients with COVID-19 lead to a more severe course of the disease (length of hospital stay, need for oxygen therapy) and the risk of overall mortality.